Motorcycle alarm with code lock / Mohamad Afiq Mohamad Amir & Muhammad Noor Ikhwan Zakaria - Mohamad Amir, Mohamad Afiq; Zakaria, Muhammad Noor Ikhwan (2015)
Nowadays, the motorcycle theft around student in university are on the rise. This is because for some people with short thinking likely to steal the motorcycle without thinking what happened to the owner of the motorcycle. So, we have think to solution to decrease the number of theft around these people. This alarm motor with code lock is designed to see the reaction between alarm circuit and code lock circuit in order to decrease the number of theft that is on rise around the university but this alarm motor also still can be uses to society. The aim of our project is to help some of the victims to security their motorcycle and can prevent the theft from happen for the second time to him. Alarm motor with code lock also helps everyone that park their motorcycle with no worries. After completion of the manufacturing process of this project , this project has been tested to ensure functionality works well. This project also has been tested to see the output is same with the assumption or not. Praise to Allah SWT, our project was successfully done. It is observed that the gain is improved when the code lock circuit is successfully connect to the alarm circuit.